(untitled) (Research, Society and Development, 2020)
Currently the use of teaching tools, in the form of qualitative models, is facilitating the learning of engineering students. Often these models are marketed or produced by students and teachers. Thus, the objective of this study was to evaluate the reactions of stresses, in the different models of buildings, from the construction of a model of seismic table and a building structure of five floors spaced from each other in two ways (0.2 and 0 , 3m). The seismic simulator was built with a wooden MDF platform, where aluminum rails were fixed to serve as a guide for the pulleys fixed on another upper platform. The upper platform was connected to an MDF disk through a steel rod. The function of this disc was to allow the horizontal oscillatory movement of the upper base, being driven by an electric screwdriver. The experimental results indicated that the simulator table was able to reproduce the seismic effects in the structural models, as well as the proof of these results by the students through mathematical calculations that demonstrated the different levels of expansion suffered when the building models were subjected to different spacing between floors. In general, it was found that the model studied can be used, satisfactorily, as a didactic support tool in the classes of structural analysis disciplines, such as general mechanics, structural theory, among others that analyze the seismic forces on a structure built up.